Application of Fiscal Incentives for Development of East Natuna Gas Field for Long-Term National Natural Gas Demand - Batubara, Marwan; Purwanto, Widodo Wahyu; Fauzi, Akhmad (Makara Journal of Technology, 2015)
East Natuna gas field, which has proven reserves of 46 trillion cubic feet, is projected to meet long-term natural gas needs. However, CO2-content of the gas reserves reaches 71%, leading to expensive development costs. This research investigates the feasibility of the field based on several fiscal incentives. Firstly, gas supply-demand until year 2040 was analyzed. Then, based on the analysis, the field was developed using high CO2 gas separation technology to produce gas of 1300 MMSCFD in 2023, 2600 MMSCFD in 2031, and 3900 MMSCFD in 2039. Finally, the economic feasibility was assessed using cash flow analysis in accordance with Indonesia’s production sharing contract scheme. The results show that the supply-demand gap continues to increase and thus the development is urgently needed. The development cost is estimated around US$ 27.59 billion. The gas selling prices are assumed at US$ 8/MMBTU for wellhead, US$ 11/MMBTU for pipelines, and US$ 11/MMBTU for LNG. To achieve minimum IRR value of 12%, the government needs to offer incentives of 30-year contract period, profit sharing of 55%: 45%, first tranche petroleum to 10%, and tax holiday of 10 years. Toll fee for Natuna-Cirebon pipeline is US$ 2.3/MMBTU at IRR of 12.6%.